Evaluation of a community-based, hybrid STEM family engagement program at pre-kindergarten entry - Zucker, Tricia; Mesa, Michael P.; DeMaster, Dana; Oh, Yoonkyung; Assel, Michael; McCallum, Cheryl; Bambha, Valerie P. (Frontiers in Education, 2024)
Introduction This article investigates an early STEM family engagement program offered during the pre-kindergarten (pre-k) year. Pre-k is an important juncture for community organizations to support children’s STEM engagement and parental involvement in informal STEM learning. We evaluated a program called Teaching Together STEM, which offers a series of museum outreach and family events at schools with the aim of broadening access to early STEM for children experiencing poverty. We replicated program content previously delivered using in-person events but shifted to a hybrid delivery approach that combined two virtual and two in-person events with linguistically diverse families of 3- and 4-year-olds. We evaluated whether attending events improved parent outcomes, such as involvement in STEM activities at home, and child outcomes, such as engagement in a STEM task. Methods The analytic sample included 59 families—35 randomly assigned families took part in the treatment and 24 families were assigned to a waitlist control group. Developed in Spanish and English, the informal STEM program was hosted by local children’s museum educators for 21 pre-k classrooms using these components: (a) a series of four family education “funshops;” (b) parent tips and reminders via text message; (c) nine thematically related, take-home STEM extension activity kits; and (d) a family museum field trip for each school, as well as individual family museum passes. Results There were no significant impacts on primary outcomes of parent involvement (effect size [ES] = −0.03) or child STEM engagement/enthusiasm (ES = −0.73). There were improvements in some aspects of parents’ STEM attitudes (e.g., math expectancy ES = 0.58), but other distal parent and child outcomes were not significantly changed. Discussion The hybrid delivery approach showed promise in terms of attendance and parent satisfaction but likely was not intensive enough to increase parent involvement. We discuss implications for other community-based family engagement programs focused on broadening participation in informal STEM.